Corporate Governance and CSR Disclosure: Earnings Management as Moderating Variable - Azwa Maqfira; Zaitul Zaitul; Yeasy Darmayanti; Mardiana Azizah; Desi Ilona (Universitas 45 Surabaya, 2024)
The purpose of this study is to examine the moderating influence of earnings management on CSR disclosure as it relates to corporate governance. From 2014 to 2018, firms in the mining sector that were listed on the Indonesia Stock Exchange were the subject of this study. In order to check for consistency in the outcomes, this study additionally employs two control variables. Theories are developed using prior research, agency theory, and legitimacy theory. Of the 110 companies in the population, 22 were chosen as the study's sample. Purposive sampling with moderated regression analysis (MRA) was the strategy used. According to the regression analysis, managerial ownership has a negative impact on CSR disclosure, while institutional ownership and the board of directors have a positive effect. On the other hand, CSR disclosure is unaffected by the audit committee and independent board of commissioners. The relationship between CSR disclosure and corporate governance cannot be mediated by earnings management.